Volume 2: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-54336
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Innovative Methods for Erosion Testing a Russian Coating on GE T64 Gas Turbine Engine Compressor Blades

Abstract: The US Navy became aware of a Russian erosion-resistant compressor coating in 1991. The coating was being applied to compressor airfoils on the TV2-117 engine (MI-8 helicopter). Performance data obtained from the Russian coating company showed greatly improved erosion resistance, leading to better engine performance and longer time-on-wing. A proposal was sent to the Foreign Comparative Testing (FCT) office to evaluate the coating for US Navy engines operating in sandy environments. The project was approved an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The Cr-Si-N coating with C Si = 11.6 at.% presents a texture change from (111) to (200), indicative of coating densification because (111) textured coatings typically possess a more opened structure, with more voids between the columns [229]. The important decrease of d g combined with the change in texture seems to indicate that for this latter coating, the limit of solubility has been exceeded and that segregation of SiN x around CrN grains has occurred, changing the growth mechanism [4][5][6][7][8]. This nanostructural change resulting in microstructural densification seems to lead to an increased H v with a related decrease in ER 90 .…”
Section: A4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cr-Si-N coating with C Si = 11.6 at.% presents a texture change from (111) to (200), indicative of coating densification because (111) textured coatings typically possess a more opened structure, with more voids between the columns [229]. The important decrease of d g combined with the change in texture seems to indicate that for this latter coating, the limit of solubility has been exceeded and that segregation of SiN x around CrN grains has occurred, changing the growth mechanism [4][5][6][7][8]. This nanostructural change resulting in microstructural densification seems to lead to an increased H v with a related decrease in ER 90 .…”
Section: A4 Discussionmentioning
confidence: 99%
“…A full engine test conducted by the US Navy [6], in conjunction with the University of Cincinnati, showed the highly protective nature of the soviet developed SPE protective coatings based on a Ti/TiN multilayer structure. In that study, half of the compressor blades were coated and after more than 7 kg of ingested sand, these were relatively unworn when compared to the uncoated blades (Figure 1.3).…”
Section: List Of Tablesmentioning
confidence: 99%
“…In works of Hamed et al (2004), Kline and Simpson (2004), and Wang et al (2014) is found that degree of erosion is a function of the angle at which the fluid droplets enter in the inter-blade passage, their speed and size.…”
Section: Condensation In Turbine Stagesmentioning
confidence: 99%
“…Currently, test methods for compressor coating evaluation using realistic conditions have been minimal. Linear cascade testing of 3-4 stationary coated blades has also been conducted: Klein and Simpson [5] and Tabakoff and Mason [6]. How ever, this is very expensive and impractical for most organizations to carry out.…”
Section: Introductionmentioning
confidence: 99%